Safety and immunogenicity of 15-valent pneumococcal conjugate vaccine (PCV-15) compared to PCV-13 in healthy older adults. Issue 3 (4th March 2019) - Stacey, Helen L.; Rosen, Jeffrey; Peterson, James T.; Williams-Diaz, Angela; Gakhar, Vanita; Sterling, Tina M.; Acosta, Camilo J.; Nolan, Katrina M.; Li, Jianing; Pedley, Alison; Benner, Patrice; Abeygunawardana, Chitrananda; et al.
ABSTRACT: Background: Pneumococcal disease remains a public health priority in adults. Safety and immunogenicity of 2 different formulations of 15-valent pneumococcal conjugate vaccine (PCV15) containing 13 serotypes included in 13-valent pneumococcal conjugate vaccine (PCV13) plus 2 additional serotypes (22F and 33F) were evaluated in adults ≥ 50 years (V114-006; NCT02547649). Methods: A total of 690 subjects (230/arm) received a single dose of either PCV15 Formulation A, PCV15 Formulation B, or PCV13 and were followed for safety for 14 days postvaccination. Serotype-specific opsonophagocytic activity (OPA) geometric mean titers (GMTs) and Immunoglobulin G (IgG) geometric mean concentrations (GMCs) were measured immediately prior and 30 days postvaccination. Results: Both PCV15 formulations had generally comparable safety profiles to PCV13. Baseline IgG GMCs and OPA GMTs were comparable across vaccination groups. At 30 days postvaccination, both PCV15 formulations induced serotype specific antibodies to all 15 serotypes in the vaccine. IgG GMCs and OPA GMTs in recipients of either PCV15 formulation were non-inferior (≤ 2-fold margin) to those measured in recipients of PCV13 for shared serotypes and superior (> 1.0-fold difference) for serotypes unique to PCV15. Formulation B generally induced higher immune responses than Formulation A. Conclusion: In healthy adults ≥ 50 years of age, both new formulations of PCV15 displayed acceptable safety profiles and induced serotype-specific immune responses comparable to PCV13.